Deletion of Endo-β-1,4-Xylanase VmXyl1 Impacts the Virulence of Valsa mali in Apple Tree - Yu, Chunlei; Li, Ting; Shi, Xiangpeng; Saleem, Muhammad; Li, Baohua; Liang, Wenxing; Wang, Caixia (Frontiers in Plant Science, 2018)
Valsa mali, a parasitic fungus, is a destructive pathogen of apple tree that causes heavy economic losses in China. The pathogen secretes various cell wall-degrading enzymes (CWDEs) that degrade plant cell-wall components, and thus facilitate its entry into host cells. Therefore, functional analysis of the genes encoding CWDEs is necessary to understand virulence of V. mali toward apple tree. Here, we identified and cloned an endo-β-1,4-xylanase gene, VmXyl1 in V. mali. The full-length cDNA of VmXyl1 is 1626 bp containing 5′- and 3′-non-coding regions, as well an open reading frame of 1320 bp that encodes a protein with a calculated molecular mass and an isoelectric point of 43.8 kDa and 4.4, respectively. The predicted amino acid sequences showed significant homology to a family GH10 of glycosyl hydrolases. The apple branch extract and beechwood xylan, but not glucose, induced the expression of VmXyl1. Furthermore, VmXyl1 had high expression levels in the apple tree bark during the pathogen infection. The deletion of VmXyl1 did not affect mycelia growth; however, it significantly reduced pycnidia formation in V. mali. The deletion strains showed a reduced virulence toward apple leaves and twigs. Moreover, the mutant strains had reduced endo-β-1,4-xylanase activity and growth when cultured using beechwood xylan as the only carbon source. Reintroducing wild-type VmXyl1 into the mutant strains rescued the defect phenotype. We conclude that VmXyl1 determines the virulence of V. mali toward apple tree. These results provide valuable insight into the plant–pathogen molecular interactions.